THE INFLUENCE OF FREE SHIPPING OFFERS AND SHOPEE ADVERTISEMENTS ON PURCHASING DECISIONS FOR FACULTY OF ECONOMICS, PANCA MARGA UNIVERSITY PROBOLINGGO STUDENTS - Yayuk Indah Ningtyas; Agung Yatiningrum; Dwi Rizqy Husnia Devi; Sheilla Fitri Dahlianti (Transpublika Publisher, 2025)
The objective of this study is to investigate how free shipping deals and Shopee adverts impact the buying choices of students studying at Panca Marga University's Faculty of Economics in Probolinggo. Specifically, it explores both the combined and individual effects of these promotional strategies. A quantitative, descriptive approach was adopted, with data gathered via questionnaires distributed to a randomly selected sample of students. The study employed various analytical tools, including validity and reliability tests, alongside classical assumption tests such as multicollinearity, heteroscedasticity, autocorrelation, and hypothesis testing. Results from the validity test confirmed all questionnaire items were valid (r > 0.197), while the reliability test yielded consistent outcomes (Cronbach’s alpha > 0.60). The data was normally distributed as per the normality test. Multicollinearity analysis showed no significant correlation among independent variables, indicating a robust regression model. Additionally, tests for heteroscedasticity and autocorrelation confirmed the absence of both issues. Hypothesis testing using the t-test revealed that the free shipping promotion significantly influenced purchasing behavior (t = 4.09 > t-table = 1.985, sig. = 0.048 ≤ 0.05). Likewise, Shopee advertisements demonstrated a notable effect on purchasing decisions (t = 2.407 > t-table = 1.985, sig. = 0.000 ≤ 0.05). Overall, the findings suggest that both free shipping offers and Shopee advertising play a significant role in shaping consumer choices among university students.